Angiolymphoid Hyperplasia With Eosinophilia - Ninan Shiby; Paul Kingsly; Gupta Ashish Kumar; Austin P C (Wolters Kluwer Medknow Publications, 2004)
We present three cases of the uncommon condition, angiolymphoid hyperplasia with eosinophilia. Two of them had lesions over pinna and external auditory canal while the third one had subcutaneous lesions with involvement of muscles over cheek and submandibular region.